Europe Against the Left? On Legal Limits to Progressive Politics - Bojan Bugaric (London School of Economics and Political Science (LSE), European Institute, 2013)
The EU »economic constitution« systematically biases EU policy making in a neo-liberal direction. Historically speaking, this was not the intent of the EU founding fathers. The original constitutional settlement of embedded liberalism was significantly redefined in the next major revisions of the Rome Treaty. The neo-liberal foundations of the single market and the EMU have imposed real and significant institutional constraints for progressive policy making. However, the role of the European Left was crucial in this alteration of the EU constitutional order. Despite the strong neoliberal consensus among the key political actors of that time, such a change would have not be possible without the Left' retreat towards »centre-leftism«, particularly in France. Furthermore, while constraints of the EU economic constitution are significant, we should avoid the »naturalization« of the EU project. The European Left, while in power, failed to leave its distinct imprint on the EU economic constitution. The Left policy agenda remained firmly embedded in the logic of the nation state. The euro crisis pushed these developments even further and, for the first time in the EU history, explicitly challenged the constitutional balance of the EU legal order. The new Austerity Union, a project in the making, profoundly altered this constitutional balance.
Keywords: 330; Constitutional law; EU economic constitution; European left; neo-liberalism; Austerity Union